The blending of standard English with African American ebonics : accommodating to each other - Holloway, Laura (My University, 2011)
This study investigates the perception of speaking Ebonics in situations in a classroom, at work and at an informal social event. Using communication accommodation theory, this investigation into African American communication focuses on whether individuals would adapt to persons who speak differently. The participants are students at a mid-western American university with the majority of the population Caucasian American. Three conditions of Ebonics were displayed 1) light Ebonics, 2) none (Standard English) and 3) heavy Ebonics. The results indicate a perception of using heavy/light Ebonics in the classroom and at work less appropriate. Speaking Standard English was perceived as the more appropriate dialect over the heavy and light Ebonics conditions. Additionally, the results suggest a tendency for participants to diverge from the heavy/light Ebonics conditions and less from the Standard English condition. These results could be used to decrease problems associated with inter-ethnic communication.
This file was last viewed in Adobe Reader X
Keywords: Black English--United States; English language--United States; Communication--Social aspects--United States; United States--Race relations--Psychological aspects